Adaptation to land scarcity among small-scale farming households in South Kivu in the Democratic Republic of the Congo - Bahati Shamamba, Dieudonné; Bashangwa Mpozi, Bosco; Egesa, Andrew Ogolla; Basengere, Espoir Bisimwa (Frontiers in Sustainable Food Systems, 2023)
Rural farming households in Sub-Saharan Africa, facing limited land access, engage in land purchase, rental, and other land access practices. However, the highly unregulated land markets expose these farmers to wide-ranging vulnerabilities. In this study, we investigated the land access mechanisms and the related constraints among the small-scale farmers in the densely populated Eastern part of The Democratic Republic of the Congo (DRC). We randomly selected 240 consenting farmers for inclusion in the study and collected data using semi-structured interviews to obtain data on land access characteristics. Then, the data was subjected to descriptive statistics to obtain measures of central tendency and dispersion on the responses and correlation statistics to understand the patterns and relations of factors affecting the land access and strategies used to cope with the limited land situation in the South Kivu province of DRC. Our results showed an insecure land tenure system among smallholder farmers. Most of the farmers in the study purchased and leased land to cope with poor land access and, in so doing, faced high price-related limitations that were unsustainable to these farmers; they also faced highly restrictive leasehold contracts. Given the limited access to financial resources and support, improving regulations of land markets and resource support interventions could promote land access among these smallholder farmers. We conclude that the challenges of land access and the current methods farmers use to obtain additional land among the smallholder farming households in the south Kivu province of DRC are precarious and unsustainable and continue to pose a food insecurity and poverty risk among these farmers. We recommend developing and implementing measures to support resource access by these farmers, such as finance, farmer-focused cooperative societies, and better land policy reforms and tenure systems to improve access to land among these farmers and farmers facing similar scenarios in other parts of sub-Saharan Africa.